Development of gifted youth in Ukraine during wartime - Sharova, Tetiana; Шарова, Тетяна Михайлівна (My University, 2024)
EN: The article emphasizes that a crucial aspect of the development of gifted youth during wartime is the creation of a favorable environment for talent cultivation. Another important aspect is the promotion of patriotic values and civic consciousness in the development of gifted youth during wartime. It is essential for the youth to understand the significance of their contribution to their country so that they can actively participate in societal building in the future. Despite the difficulties and challenges faced by gifted children in conflict situations, their potential and talents can become a key resource for the recovery and development of the country in the long run. It is emphasized that ensuring access to quality education and development for gifted youth is crucial, along with creating a favorable social and psychological climate for their improvement. /// UA: У статті наголошено на тому, що важливим аспектом розвитку обдарованої молоді у воєнний час є створення сприятливого середовища для розвитку талантів. Важливим аспектом розвитку обдарованої молоді у воєнний час є поширення патріотичних цінностей та громадянської свідомості. Молоді потрібно розуміти важливість їхнього внеску у свою країну, щоб у майбутньому вони могли брати активну участь у будівництві суспільства. Незважаючи на труднощі та виклики, з якими стикаються обдаровані діти в умовах конфлікту, їх потенціал та таланти можуть стати ключовим ресурсом для відновлення та розвитку країни у подальшому. Наголошено на тому, що важливо забезпечити доступ обдарованої молоді до якісної освіти та розвитку, а також створити сприятливий соціальний та психологічний клімат для їхнього вдосконалення.
Keywords: gifted youth; patriotism; innovation; contemporary youth needs; civic consciousness; wartime; обдарована молодь; патріотизм; інновації; потреби сучасної молоді; громадянська свідомість; воєнний час